1994
DOI: 10.1002/neu.480251110
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor

Abstract: Ciliary neurotrophic factor (CNTF) was first identified and partially purified from embryonic chick eye tissues. Subsequently, it was shown that CNTF is also present in large amounts in sciatic nerves of adult rats and rabbits, which led to its final purification and cloning. CNTF is not secreted by the classical secretory pathway involving the endoplasmatic reticulum and Golgi complex, but can be detected in high quantities within the cytoplasm of myelinating Schwann cells and astrocytes using immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(147 citation statements)
references
References 126 publications
(96 reference statements)
3
139
1
4
Order By: Relevance
“…Another cytokine that has been identified to mediate pericyte recruitment in the lung (Liu et al, 2010), retina (Pi et al, 2011) and kidney (Ren et al, 2013) in response to injury is ciliary neurotrophic factor (CNTF). CNTF is a neurotrophic factor which primarily functions in the differentiation, survival and regeneration of neurons (Sendtner et al, 1994). In a study investigating kidney fibrosis, CNTF produced at the site of injury activated a migratory phenotype and recruited pericytes via LRP-6/WNT ligand and JNK-dependent signalling (Ren et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 99%
“…Another cytokine that has been identified to mediate pericyte recruitment in the lung (Liu et al, 2010), retina (Pi et al, 2011) and kidney (Ren et al, 2013) in response to injury is ciliary neurotrophic factor (CNTF). CNTF is a neurotrophic factor which primarily functions in the differentiation, survival and regeneration of neurons (Sendtner et al, 1994). In a study investigating kidney fibrosis, CNTF produced at the site of injury activated a migratory phenotype and recruited pericytes via LRP-6/WNT ligand and JNK-dependent signalling (Ren et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 99%
“…Finally, astrocyte response to injury is altered in CNTF-knock out mice, despite compensation by other cytokines (Martin et al, 2003). Therefore, in addition to its well known neuroprotective function (Sendtner et al, 1994;Sleeman et al, 2000), CNTF appears as a potent endogenous activator of astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether endogenous CNTF plays a physiologic role in weight control is questionable, as most studies show that both mice and humans lacking CNTF are not obese. 10,11 While CNTF is present in Schwann cells and astrocytes, 5,6 it is not released into the peripheral circulation under normal conditions 7,8 and, since the predicted human CNTF protein contains no signal peptide, it raises the question of how CNTF would be released. It is possible that CNTF is only released locally under pathological conditions, such as during nerve injury to promote neuronal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dittrich et al 23 observed uptake of exogenous CNTF into the liver, and other non-neuronal cells are responsive to CNTF. 7 O'Dell et al 12 hypothesized and found that the absence of endogenous CNTF as a result of homozygosity for the CNTF null allele results in a diminished initiation of anorectic pathways, with a consequent increase in body mass in those with the A/A genotype. O'Dell et al 12 reported 10 kg higher weight and 3 kg/m 2 higher BMI in nine older Caucasian men with the A/A genotype compared to those with the G/G genotype (n ¼ 407).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation